SELF-MANAGEMENT: ASPEK PENTING DALAM MENINGKATKAN PRESTASI AKADEMIK MAHASISWA - Jenni Marlina (Jurnal Alternatif Wacana Ilmiah Interkultural, 2023)
This writing will provide an explanation of the idea and importance of self-management, along with various practices that can be utilized by students. The goal is to provide practical guidelines that can assist students in improving their self-management skills, such as effective time management, task management, self-control, and stress management. This research is a qualitative study conducted through a literature review, utilizing books and previous research findings as the primary sources. Learning discipline is highly crucial in the realm of education to achieve good academic performance. Self-management techniques have proven to be effective in aiding students to become more disciplined in their studies. Students can enhance their academic outcomes by implementing consistent learning discipline, overcoming procrastination, and managing tasks proficiently. One of the pivotal skills to attain optimal academic achievements is self-management. Self-management is an individual's ability to arrange time, regulate oneself, and plan appropriate actions to achieve personal goals. In the academic context, self-management becomes a crucial aspect underlying a student's performance and achievements.   [Tulisan ini akan memberikan penjelasan tentang ide dan pentingnya self-management, serta berbagai praktik yang dapat digunakan oleh Mahasiswa. Tujuannya adalah untuk memberikan pedoman praktis yang dapat membantu mahasiswa menjadi lebih baik dalam manajemen diri mereka sendiri, seperti pengaturan waktu yang efektif, manajemen tugas, pengendalian diri, dan pengelolaan stres. Penelitian ini adalah penelitian kualitatif yang bersifat studi pustaka yang menggunakan buku-buku dan hasil penelitian terdahulu sebagai objek yang utama. Kedisiplinan belajar sangat penting dalam dunia pendidikan untuk mencapai prestasi akademik yang baik. Teknik manajemen diri telah terbukti efektif dalam membantu Mahasiswa menjadi lebih disiplin dalam belajar. Mahasiswa dapat meningkatkan hasil akademik mereka dengan menerapkan kedisiplinan belajar yang konsisten, mengatasi prokrastinasi, dan mengelola tugas dengan baik. Salah satu keterampilan yang krusial untuk mencapai prestasi akademik yang optimal adalah self-management atau pengelolaan diri. Self-management merupakan kemampuan individu untuk mengatur waktu, mengatur diri, dan merencanakan tindakan yang sesuai untuk mencapai tujuan pribadi. Dalam konteks akademik, self-management menjadi aspek penting yang mendasari kinerja dan prestasi mahasiswa.]